Reducing Acneiform Rash Induced by EGFR Inhibitors With Honeysuckle Therapy: A Prospective, Randomized, Controlled Study - Liu, Zhen; Tian, Tian; Wang, Binbin; Lu, Demin; Ruan, Jian; Shan, Jianzhen (Frontiers in Pharmacology, 2022)
Background: Epidermal growth factor receptor inhibitors (EGFRIs), including cetuximab, erlotinib, gefitinib and icotinib, have been proven to be effective in treating colorectal cancer or lung cancer. However, most of patients who receive EGFRIs treatment experience cutaneous toxicities, such as acneiform or papulopustular rashes, which affects quality of life and leads to discontinuation of cancer therapies. Honeysuckle is a traditional herb historically used to treat skin rash for thousands of years in Eastern Asia and showed proven safety in human. Methods: To investigate whether honeysuckle therapy could control EGFRIs induced acneiform rashes, a total of 139 colorectal and lung cancer patients with EGFRIs treatments were recruited in a prospective study. Patients were randomized to 3 arms (Arm A: prophylactic treatment with honeysuckle before rash occurred; Arm B: symptomatic treatment with honeysuckle when rash occurred; Arm C: conventional treatment with minocycline and a topical solution when rash occurred). The incidences, severities and recovery time of acneiform rash were observed in each arm. Results: Honeysuckle treatment reduced incidences of EGFRIs induced acneiform rash, which were 56.5, 68.1 and 71.7% in Arm A, B and C, respectively (p = 0.280). Severities of rash (CTCAE grade 2 and 3) were significantly lower in prophylactic honeysuckle treatment (Arm A) compared to conventional treatment (Arm C) (p = 0.027), which was 10–21%, respectively. Patients with honeysuckle treatment recovered more quickly from pruritus, the median time was 22, 36 and 58 days in Arm A, B and C, respectively (p = 0.016). Conclusion: Honeysuckle was effective in reducing incidences and severities of EGFRIs induced acneiform rash, especially for prophylactic treatment.